Financial toxicity in people with chronic kidney disease undergoing hemodialysis treatment - Emanuele Cristina de Sousa Silva; Maria de Fátima Mantovani; Luciana de Alcantara Nogueira; Mahara Louise Küchler; Christian Carla Aparecida Volski Cassi; Luciana Puchalski Kalinke (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to assess the financial toxicity of people with chronic kidney disease undergoing hemodialysis treatment. Method: a descriptive analytical cross-sectional study, carried out with 214 people, between February and May 2022. For data collection, a sociodemographic and clinical instrument and the COmprehensive Score for financial Toxicity were used. For analysis, the Odds Ratio, ANOVA and Cronbach's alpha tests were used. Results: the mean financial toxicity score was 20.30. Women with a monthly family income of at most two minimum wages are more likely to have some degree of financial toxicity (Odds Ratio: 0.85; 0.76). Conclusion: financial toxicity was identified to different degrees and varied according to sociodemographic and clinical characteristics. Measuring financial toxicity can help nurses plan care and develop strategies to avoid interrupting treatment.